HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA DENGAN KEPATUHAN MENGKONSUMSI TABLET Fe DI WILAYAH PUSKESMAS RI KARYA WANITA PEKANBARU TAHUN 2017 - .S, Tesi Triska, Putri Wulandini (Jurnal Martenity and Neonatal, 2018)
Anemia in pregnancy can have an impact that is not good for the mother, either during pregnancy, delivery and during the postpartum period and subsequent periods. In pregnant women, the state of deficiency of iron (Fe) can cause miscarriage, the baby is born prematurely, the baby of low birth weight (LBW), bleeding before and during childbirth and even maternal and infant mortality are the risks faced by pregnant women who have severe anemia. Knowledge is one of the factors that influence the formation of health behavior. Non-compliance of pregnant women taking iron tablet may reflect what are the chances of developing anemia. This study aims to determine the relationship of knowledge about anemia with pregnant women taking iron tablet compliance. This research is an analytic, the population is taken that all pregnant women at health centers Karya Wanita RI 2016 and a sample of 66 people. Knowledge and compliance assessment using questionnaires. Results obtained penelitiam 56.1% of respondents knowledgeable baahwa bad and there are 50% of respondents obedient. The statistical test using chi-square test was obtained p-Value = 0.181 (p> 0.05). Conclusion no significant relationship between the knowledge of pregnant women about taking compliance anemia with iron tablet. RI PHC work Tassel Women Pekanbaru to provide counseling and health education to the community especially pregnant women about the importance of eating anemia and iron tablet regularly.